Education and Training on the Utilization of Kitchen Spices as Antivirus And Imune Booster Drinks For Motherhoods Community In Pasir Nan Tigo, Koto Tangah District, Padang City - Melindra Mulia (Fakultas MIPA Universitas Negeri Padang, 2021)
This community service aims to increase the knowledge and skills of the community in processing various kitchen spices into nutritious herbal drinks in an effort to maintain and increase family immunity during the Covid19 pandemic in Pasir Nan Tigo Village, Koto Tangah District, Padang City. The activity was carried out in the Pertapalah community showroom, Pasir Nan Tigo Village, Koto Tangah Subdistrict, Padang City and involved 14 participants. The activities were implemented in two stages, namely guided and independent activities. In the guided activities, interactive enlightment and experiment methods were done. In the independent activities, participants within groups did the practice of making drinks from spices. Results showed that the participants’ knowledge about spices and their processing to become nutritious spices improved. The participants were also interested in producing and consuming the spice drinks made.